Frontal Sinus Mucocele After Osteoplastic Flap Surgery: Case Report - Catalano, Peter; Schlewet, Michael (Archives of Clinical and Medical Case Reports, 2017)
A mucocele of paranasal sinuses is a collection of mucus within an epithelial lined sinus whose outflow tract is permanently obstructed. The most common site for a mucocele is the frontal sinus; it is less common in the other sinuses. Frontal mucoceles present in different ways depending upon their size and duration, with symptoms often gradual and insidious. Symptoms are mainly ophthalmic and include proptosis and diplopia. The diagnosis is established by history, physical exam, and imaging studies (primarily Computerized tomography of the paranasal sinuses). Herein, we present a case of a frontal mucopyocele (type 5a) that occurred 25 years after a frontal sinus osteoplastic flap operation. Successful treatment involved endoscopic marsupialization followed by the use of a drug-eluting sinus stent to maintain ostial patency during the early post-op phase.